2018
DOI: 10.14527/pegegog.2018.032
|View full text |Cite
|
Sign up to set email alerts
|

The effects of parent-involved science activities on basic science process skills of the children in the age group of 5-6

Abstract: This study aims to examine the effects in science activities including parent involvement activities, concerning the science process skills of children aged 5-6, attending pre-school, and analyses the obtained information regarding the views of the parents involved in the program. The study group consisted of 30 children in the 5-6 age group, and 15 parents who were attending lessons. The embedded mixed method design was used in the study. Quantitative data was collected by a pre-school science process skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a study of family conversations Crowley et al (2021) noted an important finding of gender disparity, finding that parents were three times more likely to explain science to boys than girls when using interactive science exhibits at a museum. There are experimental studies indicating that science education with family participation is effective in improving the scientific process skills of preschool students (Ulutaş and Kanak, 2018;Yılmaz et al, 2018). It has been found that students' success is positively affected by interactive assignments shared by families in secondary school (Van Voorhis, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In a study of family conversations Crowley et al (2021) noted an important finding of gender disparity, finding that parents were three times more likely to explain science to boys than girls when using interactive science exhibits at a museum. There are experimental studies indicating that science education with family participation is effective in improving the scientific process skills of preschool students (Ulutaş and Kanak, 2018;Yılmaz et al, 2018). It has been found that students' success is positively affected by interactive assignments shared by families in secondary school (Van Voorhis, 2003).…”
Section: Resultsmentioning
confidence: 99%